Climate protection and a new operator: The Eastern German lignite industry is changing - Pao-Yu Oei; Hanna Brauers; Claudia Kemfert; Christian von Hirschhausen; Dorothea Schäfer; Sophie Schmalz (DIW Economic Bulletin, 2017)
According to the German federal government's climate protection targets, there will be a continuous reduction of lignite-based electricity well before 2030. Simulations show that the currently authorized lignite mines in eastern Germany would not be fully depleted if the climate protection targets for 2030 were complied with. This makes planning for new mines or the expansion of existing ones superfluous. For the planning security of all the actors involved, policy makers should bindingly exclude permits for additional surface mines. In terms of the follow-up costs of lignite mining, the issue is whether or not the companies' provisions are high enough and insolvency-proof. In this context, the new ownership structures in the eastern German lignite industry, after Vattenfall's sale of its lignite division to Czech Energeticky a Prumyslovy Holding (EPH), have become a matter of importance. Simulations show that only under optimistic assumptions, the current provisions of 1.5 billion euros for the Lusatian lignite region are sufficient to cover recultivation costs. However, alternative scenarios show significant shortfalls. For this reason, policy makers should work toward independent, transparent cost estimates. Additional measures should be considered as required, such as the creation of a public sector fund to permanently protect the general public against being forced to take on the costs of recultivation. This is also animportant theme for the government's new Commission on Growth, Structural Change, and Regional Development (Kommission Wachstum, Strukturwandel und Regionalentwicklung). Individual federal states also have key roles to play in the creation of a dependable roadmap for a coal phase-out. For example, the government of Brandenburg is now in the process of revising its energy strategy for 2030 (Energiestrategie 2030).
Keywords: Q48; Q52; L71; L94; G31; G34; 330; coal; lignite; climate policy; Germany; liabilities; energy transition